35y² - 42y + 14 = 0
Resolva a equação por Bhaskara
Soluções para a tarefa
Respondido por
2
Primeiro você pode simplificar a equação, divida por 7
5y² - 7y + 2 = 0
![\frac{-b +- \sqrt{ b^{2} -4ac} }{2a} \frac{-b +- \sqrt{ b^{2} -4ac} }{2a}](https://tex.z-dn.net/?f=+%5Cfrac%7B-b+%2B-++%5Csqrt%7B+b%5E%7B2%7D+-4ac%7D+%7D%7B2a%7D+)
![\frac{7 +- \sqrt{ 7^{2} -4.5.2} }{2.5} \frac{7 +- \sqrt{ 7^{2} -4.5.2} }{2.5}](https://tex.z-dn.net/?f=+%5Cfrac%7B7+%2B-++%5Csqrt%7B+7%5E%7B2%7D+-4.5.2%7D+%7D%7B2.5%7D+)
![\frac{7 +- \sqrt{ 49 -40} }{10} \frac{7 +- \sqrt{ 49 -40} }{10}](https://tex.z-dn.net/?f=+%5Cfrac%7B7+%2B-++%5Csqrt%7B+49+-40%7D+%7D%7B10%7D+)
![\frac{7 +- \sqrt{9} }{10} \frac{7 +- \sqrt{9} }{10}](https://tex.z-dn.net/?f=+%5Cfrac%7B7+%2B-++%5Csqrt%7B9%7D+%7D%7B10%7D+)
![\frac{7 +- 3 }{10} \frac{7 +- 3 }{10}](https://tex.z-dn.net/?f=+%5Cfrac%7B7+%2B-++3+%7D%7B10%7D+)
![\frac{10}{10} = 1 \frac{10}{10} = 1](https://tex.z-dn.net/?f=+%5Cfrac%7B10%7D%7B10%7D++%3D+1)
![\frac{4 }{10} = \frac{2 }{5} \frac{4 }{10} = \frac{2 }{5}](https://tex.z-dn.net/?f=+%5Cfrac%7B4+%7D%7B10%7D++%3D++%5Cfrac%7B2+%7D%7B5%7D+)
5y² - 7y + 2 = 0
Perguntas interessantes